2020
DOI: 10.1093/braincomms/fcaa117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on macular function and retinal structure in retinitis pigmentosa

Abstract: Retinitis pigmentosa is an inherited neurodegenerative disease of the retina. We investigated smoking as a modifiable environmental factor for the progression of this currently untreatable disease. Clinical data, smoking history, macular function, and morphology including visual acuity, visual field sensitivity, ellipsoid zone width, and central retinal thickness were investigated. Association between pack × years and these parameters were evaluated using generalized estimating equation models to adjust confou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Interestingly, despite the similar duration of diagnosis before surgery and CDR, the smoker group also had a significantly lower mean BCVA. Because of the design and scope of our study, we cannot make a valid assumption as to the impact of tobacco smoking on the affectation of the central visual field due to glaucoma; however, smoking has been found to have a negative effect on visual acuity in patients with conditions such as retinitis pigmentosa and age-related macular degeneration, in which a possible cause has been postulated to be the chronic inflammation and oxidative stress resulting in cone cell death (20) .…”
Section: Figurementioning
confidence: 99%
“…Interestingly, despite the similar duration of diagnosis before surgery and CDR, the smoker group also had a significantly lower mean BCVA. Because of the design and scope of our study, we cannot make a valid assumption as to the impact of tobacco smoking on the affectation of the central visual field due to glaucoma; however, smoking has been found to have a negative effect on visual acuity in patients with conditions such as retinitis pigmentosa and age-related macular degeneration, in which a possible cause has been postulated to be the chronic inflammation and oxidative stress resulting in cone cell death (20) .…”
Section: Figurementioning
confidence: 99%
“…However, its efficacy should be addressed in future studies. In addition, a study showed that smoking is detrimental to patients with RP, as it worsens macular function and structural integrity [32]. Hence, smoking may not benefit patients with RP.…”
Section: Rp: Intervention Strategy At An Early Stagementioning
confidence: 99%
“…Immunomodulatory therapies, whether for tumour therapy (melanoma, basal cell carcinoma), rheumatological conditions or ophthalmic diseases, may not only have ocular side-effects, but may also point to systemic conditions associated with vision problems (e. g. vitamin A deficiency associated with ulcerative colitis). Dietary and lifestyle factors should also be considered: For example, there are indications of possible negative effects on the disease course when patients with variants in the ABCA4 gene take high-dose vitamin A, or when patients with retinitis pigmentosa smoke [19,20].…”
Section: Medical Historymentioning
confidence: 99%